HUBUNGAN ANTARA CORPORATE GOVERNANCE DAN KARAKTERISTIK DIREKTUR UTAMA DENGAN KINERJA PERUSAHAAN (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2010-2011) - , KRISMAN HASINTONGAN PURBA, Prof. Dr. Indra Wijaya Kusuma, Ak., M.B.A., CMA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research aims to examine the relationship between corporate governance, chief executive officer characteristics and firm performance. Corporate governance is measured by managerial ownership, institutional ownership, the size of the board of commissioners, and the number of independent commissioners whereas for chief executive officer characteristics is measured by tenure, gender, and age. Firm performance is measured by Tobinâs Q and used as variabel control the firm size, leverage, and the number of years listing. The Sample used are manufacturing companies that listed in Indonesia Stock Exchange with periods of observation 2010-2011. Sample selection uses purposive sampling method. Using Ordinary Least Square (OLS), the results show that institutional ownership, the size of the board of commissioners, the number of independent commissioners, age, tenure, and leverage have significantly influence the firm performance.